A Histopathological Approach to a Case of Recurrent Genital Molluscum Contagiosum - Dwi Intan Yuniasih; Lita Setyowatie; Diah Prabawati Retnani (Berkala Kedokteran, 2025)
Molluscum contagiosum (MC) is a harmless, viral skin infection with a high transmission risk. The Molluscum contagiosum virus (MCV) has two primary forms: type 1 and type 2. Sexually transmitted MC affects the anogenital region, encompassing external genital organs, inner thighs, inguinal folds, and suprapubic areas. The likelihood of MC recurring after treatment can reach up to 35 percent. Transmission primarily occurs through direct physical contact. A 29-year-old man who complained of bumps on the pubis and penile shaft for 3 months accompanied by itching. Venerological examination revealed multiple, round, dome-shaped erythematous papules with and central umbilication on the pubis and penile shaft. On punch biopsy, the epidermis appears with hyperplastic squamous cell epithelium with a cup shape containing Handerson-Peterson bodies. The condition of recurrent, atypical, and mimicking lesions with condyloma lata lesions means that diagnosis in this patient requires a histopathological examination.